The effect of expander input and output pressure ratio on the performance of simple organic Rankine cycle with low quality geothermal steam as the heat source - Siregar, Achmad Husein (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
Electricity currently plays essential role to support the lives of modern society and national development in Indonesia. The use of renewable energy resources to produce electricity need to be continually encouraged since the exploitation of fossil energy sources to generate power have been depleting the energy reserves. In addition, the use of fossil energy pollutes for the environment. For these reasons, a lot of studies need to be carried out to find out the best possibilities to generate power using renewable energy sources.In this study an experimental investigation of the performance of a small-scale power generation system using an organic Rankine Cycle (ORC) system with a low-quality geothermal steam as the heat source is carried out. The experimental system was designed, built and tested using R134a as a working fluid. This small-scale power generation unit uses key components such as a vane type pump, to increase the pressure of the working fluid, the evaporator, to absorb heat from the heat source, the expander (turbine), to expand the heat vapour to generate work on shaft, and the condenser, to change the fluid phase into saturated liquid. Some parameters such as heating steam temperature and mass flow rate of the working fluid will be varied during the experiment to obtain the best system performance. From the test results it is obtained that the highest thermal efficiency of the system is 5.34% and the net output power is 1523.42 Watt. The experimental results show that using low-quality geothermal steam in the power generation system using this ORC system is feasible to use with acceptable performance. Keywords: renewable energy, geothermal, organic Rankine cycle